2007
DOI: 10.1136/pgmj.2006.052258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of fatty liver disease in the Shuiguohu district of Wuhan city, central China

Abstract: Background: Fatty liver disease (FLD) is highly prevalent in Western countries, but recent data have shown that FLD is also emerging in China. Aim: To investigate the prevalence and risk factors of FLD in the Shuiguohu district of Wuhan city, central China, during 1995China, during -2004. Methods: 12247 individuals (7179 men and 5068 women) over 18 years of age who were living in the area were investigated for FLD in the Zhongnan Hospital of Wuhan University from 1995 to 2004. FLD was determined by the ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Recently, much attention has been focused on the rising incidence of NAFLD in several Asian countries, including China, Korea, Japan, and India [11][12][13][14]. Various authors have shown that Asian patients with NAFLD display higher levels of visceral adiposity at lower body mass index (BMI) than the Caucasian population, and new BMI criteria have been created to adjust for this anthropometric difference [12,15,16].…”
Section: Epidemiologymentioning
confidence: 99%
“…Recently, much attention has been focused on the rising incidence of NAFLD in several Asian countries, including China, Korea, Japan, and India [11][12][13][14]. Various authors have shown that Asian patients with NAFLD display higher levels of visceral adiposity at lower body mass index (BMI) than the Caucasian population, and new BMI criteria have been created to adjust for this anthropometric difference [12,15,16].…”
Section: Epidemiologymentioning
confidence: 99%
“…NAFLD and NASH are closely related to obesity and insulin resistance, and are now recognized as hepatic manifestation of the metabolic syndrome [26][27][28] . Diet and lifestyle intervention are primary therapies in the management of these patients, but it is not easy for patients with NAFLD/NASH to maintain these interventions 29,30 . Several studies have been aimed to discover pharmacological treatments for NAFLD/NASH; however, despite the clinical importance, there is still a lack of consensus for pharmacological treatment on NAFLD/NASH.…”
Section: Evaluation Of Publication Biasmentioning
confidence: 99%
“…In addition, the prevalence of NAFLD in Hong Kong Chinese was 16% [21], and in an adult population of Taiwan it was 12% [22]. Of particular interest, the prevalence of fatty liver in Shanghai and Wuhan (capital of Hubei province, central China) has approximately doubled in the past 7-10 years [23,24]. Specifically, it has increased from 13% to 25% in participants of routine health examinations in the Shuiguohu district of Wuhan [24], and from 4% to 14% in Shanghai BaoSteel Group employees [23].…”
Section: Prevalence Of Nafld In Chinamentioning
confidence: 99%
“…Of particular interest, the prevalence of fatty liver in Shanghai and Wuhan (capital of Hubei province, central China) has approximately doubled in the past 7-10 years [23,24]. Specifically, it has increased from 13% to 25% in participants of routine health examinations in the Shuiguohu district of Wuhan [24], and from 4% to 14% in Shanghai BaoSteel Group employees [23]. Among the latter, the prevalence of fatty liver in participants with elevated serum alanine aminotransferase (ALT) levels (>40 U/L) increased from 26% to 51% between 1995 and 2002 [23].…”
Section: Prevalence Of Nafld In Chinamentioning
confidence: 99%